AQ-coupled few-layered g-C3N4 nanoplates obtained by one-step mechanochemical treatment for efficient visible-light photocatalytic H2O2 production. (29th April 2022) - Liu, Wei; Xu, Run; Wang, Yongye; Huang, Niu; Shimada, Toshihiro; Ye, Liqun
Abstract: Solar-driven photocatalytic H2 O2 production is a sustainable and clean technique with respect to the traditional route. Here, the efficient H2 O2 generation was accomplished by π−π coupling of AQ onto the few-layered graphitic carbon nitride (g-C3 N4 ) nanoplates through one-step mechanochemical treatment. A H2 O2 generation rate of 231 μM h −1 was obtained using AQ-coupled g-C3 N4 nanoplates under visible light illumination, exceeding that of the g-C3 N4 nanoplates and bulk g-C3 N4 by 7-time and 14-time, respectively. Experimental results showed that the high oxygen reduction efficiency could be ascribed to the enhanced surface area, more exposed active sites and the distinct AQ roles of the electrons storage and restraining the charge recombination. This work inspired future work in synthesizing H2 O2 through a sustainable and green route. Graphical abstract: g-C3 N4 nanoplates loaded redox molecules were synthesized through a scalable ball milling method. Few-layered structure and AQ coupling can boost the charge separation, offer more active sites and form a more reliable reduction medium (H2 AQ). Image 1 Highlights: AQ-coupled g-C3 N4 nanoplates were prepared by one-step mechanochemical exfoliation. The product retained the basic structure and optical properties of g-C3 N4 and is fully characterized. The product showed photocatalytic H2 O2 production 14 times better than the bulk in the visible region. The few-layered structure and AQ coupling led to boosted charge separation, more active sites and reliable reduction medium.